THE APPLICATION OF TEAM ASSISTED INDIVIDUALIZATION (TAI) USING MULTIMEDIA IN IMPROVING MATHEMATICS LEARNING ABOUT TWO-DIMENTIONAL FIGURE FOR THE FIFTH GRADE STUDENT OF SDN BULUREJO IN THE ACADEMIC YEAR 2014/2015 - Hardiyanti, Fitri (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application Of Team Assisted Individualization (TAI) Using Multimedia In Improving Mathematics Learning About Two-Dimentional Figure For The Fifth Grade Student Of SDN Bulurejo In The Academic Year 2014/2015. The objectives of this study are: (1) to describe the steps in the application of TAI using multimedia in improving mathematics, (2) to improve mathematics learning about two-dimentional figure through the application of TAI using multimedia, and (3) to describe problems and solutions in the application of TAI using multimedia. This research is collaborative Classroom Action Research (CAR) conducted in three cycles, consisting of planning, implementation, observation, and reflection on each cycle. The subject of this research was 30 students. Techniques of collecting the data in this observation, interview, study were test and documentation. The conclusions of this research is the application of the TAI type of multimedia can enhance the learning of mathematics in class V SDN Bulurejo in the academic year 2014/2015.Keywords: Team Assisted Individualization (TAI), multimedia, mathematics. Abstrak: Penerapan Tipe Team-Assisted Individualization (TAI) Dengan Multimedia Dalam Peningkatan Pembelajaran Matematika Tentang Bangun Datar Pada Siswa Kelas V SDN Bulurejo Tahun Ajaran 2014/2015. Tujuan penelitian ini adalah (1) mendeskripsikan langkah-langkah penerapan model Kooperatif tipe TAI dengan multimedia, (2) meningkatan pembelajaran Matematika tentang bangun datar melalui penerapan model Kooperatif tipe TAI dengan multimedia, (3) menemukan kendala dan solusi yang dihadapi pada penerapan model Kooperatif tipe TAI dengan multimedia.Penelitian Tindakan Kelas (PTK) kolaboratif ini dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Subyek pada penelitian ini berjumlah 30 siswa. Teknik pengumpulan data berupa observasi, wawancara, tes dan dokumentasi. Simpulan penelitian ini adalah penerapan tipe TAI dengan multimedia dapat meningkatkan pembelajaran matematika pada siswa kelas V SDN Bulurejo tahun ajaran 2014/2015. Kata Kunci : Pendekatan PMR, Peningkatan Pembelajaran, Matematika